Effects of Performance Appraisal Systems on Employee Career Development in Tunisia - Walter, Edith (European Journal of Human Resource, 2024)
Purpose: The aim of the study was to assess the effects of performance appraisal systems on employee career development in Tunisia. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that these systems provide structured and systematic methods for evaluating employee performance, identifying strengths and areas for improvement. When effectively implemented, performance appraisals offer valuable feedback that helps employees understand their progress and align their goals with organizational objectives. This alignment fosters a culture of continuous improvement and skill development, enabling employees to identify and pursue opportunities for career advancement. Moreover, performance appraisals often incorporate individual development plans that outline specific training and development activities tailored to each employee's career aspirations. These plans can include mentoring, coaching, and access to professional development resources, which are crucial for career growth. The process also facilitates open communication between employees and supervisors, promoting a clearer understanding of career expectations and potential career paths within the organization. However, the effectiveness of performance appraisal systems in fostering career development largely depends on their design and execution. Transparent, fair, and objective appraisal processes that are perceived as unbiased by employees are more likely to be effective. Implications to Theory, Practice and Policy: Goal-setting theory, social learning theory and constructivist learning theory may be used to anchor future studies on assessing the effects of performance appraisal systems on employee career development in Tunisia. Organizations should consider adopting comprehensive feedback systems that integrate multidimensional feedback, including inputs from peers, subordinates, and supervisors. It is recommended that mandatory implementation of multidimensional feedback systems be advocated across organizations.